Performance of europium aluminium doped polymer optical waveguide amplifier - Nur Najahatul Huda Saris; Azura Hamzah; Sumiaty Ambran; Osamu Mikami; Takaki Ishigure (Institute of Advanced Engineering and Science, 2019)
In this paper, the graded index (GI) multimode rare-earth metal (RE-M) doped polymer optical waveguide amplifier has been prepared and tested optically. A 10-cm Europium Aluminum Benzyl Methacrylate ( was fabricated via a unique technique known as the “Mosquito Method” which utilizes a micro-dispenser machine. Optical gain from 75 to 150 µm circular core diameter waveguide of 13 wt.% concentration has been demonstrated and measured under forward pumping condition. The cladding monomer deployed in this research is Acrylate resin XCL01, which is a modified photocurable acrylate material. Fundamentally, -30 decibel (dBm) red light signal input and 23 dBm pump power of 532 nm green laser wavelength is implemented within the range of 580 to 640 nm optical amplification wavelength. A maximum gain of 12.96 dB at 617 nm wavelength has been obtained for a 100 µm core diameter of Eu-Al polymer optical waveguide. The effect of different coupler diameter for pumping and the comparison of insertion loss before and after amplification against the performance of the Eu-Al polymer waveguide amplifier are also studied. There exists an optimum core diameter of which the amplifier gain enhancement is at maximum value.